Determination of Hexabromocyclododecane Diastereomers in Environmental Water Samples with Ionic Liquid-Dispersive Liquid-Liquid Microextraction - Wang, Xia; Hu, Cong; Cheng, Chuan-Ge; Zhao, Ru-Song (Asian Journal of Chemistry, 2015)
In this paper, a simple, rapid and sensitive method for the simultaneous enrichment and sensitive determination of hexabromocyclododecane diastereomers (HBCDs) in environmental water samples has been developed. It was based on ionic liquid-dispersive liquid-liquid microextraction (IL-DLLME) and rapid resolution liquid chromatography-electrospray tandem mass spectrometry (RRLC-ESI-MS/ MS). Important factors affecting extraction efficiencies were investigated and optimized. Under the optimal conditions, experimental results exhibited excellent linear relationships over the range of 0.1-10 μg L-1. The limits of detection and relative standard deviations were in the range of 0.008-0.035 μg L-1 and 1.18-7.58 %, respectively. The proposed method has been successfully applied for the trace analysis of hexabromocyclododecane diastereomers in environmental water samples.